Effects of Awakening and the Use of Topical Dexamethasone and Levofloxacin on the Cytokine Levels in Tears Following Corneal Transplantation - Mariann Fodor; Goran Petrovski; Dorottya Pásztor; Péter Gogolák; Éva Rajnavölgyi; András Berta (Journal of Immunology Research)
Objectives. To study the short-term effect of eye opening and use of topical dexamethasone phosphate 0.1% and levofloxacin 0.5% on the cytokine levels in human tears. Methods. Prospective experimental design was used for tear collection from eyes of 10 healthy controls and 20 patients four days after penetrating keratoplasty (PKP) at awakening and after instilling dexamethasone or levofloxacin. The concentrations of different cytokines were measured by cytometric bead array. Results. At eye opening, IL-6 levels were higher in the PKP group as compared to the controls. Thirty minutes later, the released levels of IL-10, IL-13, IL-17, IFNγ, and CCL5 increased in controls, while CXCL8 decreased in both control and PKP groups. The release of the cytokines remained stable after 30 mins except for IFNγ, which showed a decrease in the controls following levofloxacin instillation. No short-term effects of the topically used dexamethasone and levofloxacin could be detected on the cytokine levels in controls and after PKP. Conclusions. Evidence of changes in the levels and time course of tear cytokines after awakening or eye opening could be established and the short-term confounding effects of dexamethasone and levofloxacin on the levels of released cytokines in human tears could be excluded.